2018
DOI: 10.1016/j.resuscitation.2018.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to community consultation in exception from informed consent: Analysis of scope, efficiency, and cost at two centers

Abstract: Canvassing at public events was the most efficient mode of performing CC, with approval rates similar to mailings, online surveys, and canvassing in other locations. Print advertisements in local papers had a low yield and cost more than other approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
(42 reference statements)
2
13
2
Order By: Relevance
“…63 Although some reports are positive and participants satisfied, 64,65 community consultation and public disclosure are also challenging, time consuming, and costly. 66,67 A study 68 reviewed 28 completed and published acute care studies between 1996 and 2018, that used exception from informed consent or waiver of informed consent. 68 Only 359 (0•6%) of 63 947 study enrolments were withdrawn or did not provide consent for continued study participation.…”
Section: Exception From Consentmentioning
confidence: 99%
“…63 Although some reports are positive and participants satisfied, 64,65 community consultation and public disclosure are also challenging, time consuming, and costly. 66,67 A study 68 reviewed 28 completed and published acute care studies between 1996 and 2018, that used exception from informed consent or waiver of informed consent. 68 Only 359 (0•6%) of 63 947 study enrolments were withdrawn or did not provide consent for continued study participation.…”
Section: Exception From Consentmentioning
confidence: 99%
“…There were relatively few reports including assessments of effort and resources for conducting community consultation 32,42,53,54 . Where reported, costs ranged widely ($1,500 to >$80,000 per site) 41,54 .…”
Section: Resultsmentioning
confidence: 99%
“…Dickert et al reported that increased community consultation methods were associated with increased acceptance of EFIC and greater recall of study information but lower recall of risks [21]. Others have noted that public canvassing, in-person community consultation, and targeted community outreach to individuals most at risk of inclusion in the trial were the most successful methods and yielded greater acceptance rates [9,22,23].. Public disclosure and community consultation for the PAMPer trial was conducted from 2012 to 2013 and included use of radio, newspaper, and random digit dialing to zip codes eligible for enrollment, online websites, YouTube videos, and flyering. We found that while most (81.7%) participants believed community consultation was important, none of the patients or surrogates could recall being informed of PAMPer via community consultation, and none were aware of opt out procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The US Food and Drug Administration also requires a public disclosure and community consultation phase prior to beginning the trial to inform communities of the proposed study and provide ways in which individuals wishing to opt out may be excluded. It is known that the general population is largely accepting of EFIC enrollment [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and community consultation practices have been associated with increased acceptance [9,[21][22][23][24]. However, there is a paucity of studies that have characterized the experiences of patients or surrogates enrolled in the actual EFIC studies [25][26][27][28][29][30], and none have been conducted following interventions that focus on traumatic hemorrhage.…”
Section: Introductionmentioning
confidence: 99%